2002
DOI: 10.1177/109861102237689
|View full text |Cite
|
Sign up to set email alerts
|

Policing Diversity: Themes and Concerns from the Recent British Experience

Abstract: The aim of this article is to provide an overview of the recent development of the notion of “policing diversity” in England and Wales. In addition to outlining why policing diversity has become a preeminent theme in current debates about policing, the article explores central conceptual issues and argues that it does represent a fundamental break with long-standing notions such as “policing by consent.” However, it argues that, taken to its logical conclusions, the concept might raise serious problems for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The police research covers the promotion of (ethnic) diversity within the police force and also 'policing diversity' as a means of achieving legitimacy (Rowe 2002, Cashmore 2002, van Ewijk 2011, Peterson and Uhnoo 2012, Pettersson 2013), but in the private security industry, strategies concerning ethnic diversity are a new phenomenon that has not been researched. Previous research in the field of private security has focused on the actual service delivery of private security officers (Hobbs et al 2003, Wakefield 2003, Button 2007b, the 'risk gaze' or risk profiling targeting specific categories of people (McCahill 2002, Wakefield 2003, Hutchinson and O'Connor 2005 and also ethnic profiling by private security officers (Gabbidon 2003, O'Dougherty 2006, Kempa and Singh 2008, as well as public perceptions of the industry (Livingstone and Hart 2003, Noaks 2008, van Steden and Nalla 2010, Berndtsson 2011, Thumala et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The police research covers the promotion of (ethnic) diversity within the police force and also 'policing diversity' as a means of achieving legitimacy (Rowe 2002, Cashmore 2002, van Ewijk 2011, Peterson and Uhnoo 2012, Pettersson 2013), but in the private security industry, strategies concerning ethnic diversity are a new phenomenon that has not been researched. Previous research in the field of private security has focused on the actual service delivery of private security officers (Hobbs et al 2003, Wakefield 2003, Button 2007b, the 'risk gaze' or risk profiling targeting specific categories of people (McCahill 2002, Wakefield 2003, Hutchinson and O'Connor 2005 and also ethnic profiling by private security officers (Gabbidon 2003, O'Dougherty 2006, Kempa and Singh 2008, as well as public perceptions of the industry (Livingstone and Hart 2003, Noaks 2008, van Steden and Nalla 2010, Berndtsson 2011, Thumala et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of Hispanic American officers in the Chicago Police Department is steadily increasing in recent years due to continuously implementing affirmative action in the department. A study (Rowe, 2002) in England showed that the police-department-employed racial minority officers policing in diversified neighborhoods might reduce violent crimes in those communities. It is reasonable to believe that police departments will successfully recruit racial minorities, regardless of the proportion of racial minorities in the communities, if the departments continue to implement the affirmative action policies.…”
Section: Resultsmentioning
confidence: 99%
“…(P1, 2008)Her belief that numbers of females are irrelevant and personality and the individual is paramount does not fit neatly with the anti-woman in power rhetoric she had heard from front-line male officers. As she had not encountered such arguments in relation to race (see Chan et al, 2010), it seems unlikely that ethnicity would be used explicitly in this way post Macpherson (see Chan et al, 2010; Loftus, 2008; Rowe, 2002).…”
Section: The Lived Realities Of Women Police Officersmentioning
confidence: 99%